Teaching the Truth: Difficulties with Social Justice and Social Class in Graduate School - Leona English; Carole Roy (Educational Considerations, 2015)
Nowadays, anyone who wishes to combat lies and ignorance and to write the truth must overcome at least five difficulties. He must have the courage to write the truth when truth is everywhere opposed; the keenness to recognize it, although it is everywhere concealed; the skill to manipulate it as a weapon; the judgment to select those in whose hands it will be effective; and the cunning to spread the truth among such persons.
Keywords: graduate; education; Social Justice; Higher Education; and Adult Education; cultural capital shock; focus; teaching